2018
DOI: 10.3390/s18103229
|View full text |Cite
|
Sign up to set email alerts
|

A Gas Sensor Based on a Single SnO Micro-Disk

Abstract: In this study, individual nanofabricated SnO micro-disks, previously shown to exhibit exceptional sensitivity to NOx, are investigated to further our understanding of gas sensing mechanisms. The SnO disks presenting different areas and thickness were isolated and electrically connected to metallic electrodes aided by a Dual Beam Microscope (SEM/FIB). While single micro-disk devices were found to exhibit short response and recovery times and low power consumption, large interconnected arrays of micro-disks exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…It is well-known that some amount of energy (heat) is necessary to overcome the activation barrier for the chemisorption ( H Chem ), otherwise, the gas molecules would be in a physisorbed state (Batzill and Diebold, 2005). However, by Equation 1, if the temperature goes too high the coverage decreases and sensor signal drops, in full agreement with previous results involving SnO micro-disks in multi-and singledevice configurations (Suman et al, 2013;Masteghin and Orlandi, 2018). Figure 4B shows the sensor response for the SnO micro-disks at 200 • C reached through two different heating modes, external heating (red spheres), and self-heating (blue triangles).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It is well-known that some amount of energy (heat) is necessary to overcome the activation barrier for the chemisorption ( H Chem ), otherwise, the gas molecules would be in a physisorbed state (Batzill and Diebold, 2005). However, by Equation 1, if the temperature goes too high the coverage decreases and sensor signal drops, in full agreement with previous results involving SnO micro-disks in multi-and singledevice configurations (Suman et al, 2013;Masteghin and Orlandi, 2018). Figure 4B shows the sensor response for the SnO micro-disks at 200 • C reached through two different heating modes, external heating (red spheres), and self-heating (blue triangles).…”
Section: Resultssupporting
confidence: 89%
“…Figure 6B clearly shows a lower recovery time when submitted to the external heating method, as a result of both higher pre-exponential factor and more energy available. Besides, we showed that O (ads) − species still remain onto the SnO surface, after stopping the release of the NO 2 (Masteghin and Orlandi, 2018), indicated in Equation (3) (Kaur et al, 2007;Sharma et al, 2013):…”
Section: Heating Mode Sensor Signalmentioning
confidence: 94%
See 2 more Smart Citations
“…in the sensing layer. This approach is the one followed in [15,16]. In the first case, the sensing element is a microdisk of SnO.…”
Section: Review Of the Contributions In This Special Issuementioning
confidence: 99%